Development of a bioactive nanoemulsion (o/w) incorporated into the essential oil of Coleus aromaticus Benth (spearmint) (Research, Society and Development, 2022)
This study aimed to evaluate the larvicidal activity of essential oil (EO) and nanoemulsion (O/A) of Coleus aromaticus Benth (coarse mint) leaves. The plant material obtained in this research was collected in Arari (MA) in May 2021. The hydrodistillation technique was used for EO extraction in a modified Clevenger extractor system. The total phenolic compounds were determined by the Folin-Ciocalteu method. Antioxidant activity was performed by the spectrophotometric method of elimination of hydroxyl radicals from salicylic acid. For larvicidal activity, Aedes aegypti larvae were submitted to EO solutions and nanoemulsions at concentrations of 10-100 mg L-1, where larvae mortality was evaluated and LC50 was determined by the Probit method. In the total phenolic assay, the value of 350.86 mg EAT g-1 was quantified, being a significant result for the presence of the class in the essential oil. In the antioxidant activity assay, the IC50 of 195.39 mg L-1 was obtained for the action of C. aromaticus being classified as promising. The action of the EO as larvicidal was observed and the LC50 of 3.24 mg L-1 was determined, while for nanoemulsion a higher action was observed in 1.83 mg L-1. The results obtained allowed us to conclude that the studied EO presented efficient larvicidal activity against the larvae of Aedes aegypti. Finally, we highlight the potential obtained for EO and nanoemulsion obtained from the species under study, and it is important to highlight that the nanoemulsion obtained is a bioproduct formulated from the essential oil with market potential, being important in the control and combat of cases related to Aedes aegypti.